Effects of rhaponticin on retinal oxidative stress and inflammation in diabetes through NRF2/HO‐1/NF‐κB signalling. Issue 11 (14th July 2020) - Shi, Qiang; Cheng, Yuhong; Dong, Xiaomin; Zhang, Ming; Pei, Cheng; Zhang, Mingzhen
Abstract: Oxidative stress and inflammation have long been considered to be responsible for the development and progression of diabetic retinopathy. On the other hand, rhaponticin (RN) has received scientific attention due to its various pharmacological properties. Keeping all these in view, the present study was performed to investigate the potential protective effects of RN on the retina in diabetic rats. Rats were randomly divided into three groups: control group rats, diabetic group rats, diabetic + RN (20 mg/kg body weight for 28 days through oral route) group rats. RN supplementation to diabetic rats significantly prevent the reduction of final body weight loss, reduced weekly fasting blood glucose levels and HbA1c levels with a significant increase in serum insulin levels. quantitative polymerase chain reaction and immunohistochemical analysis found upregulation of Nrf2, NQO‐1, HO‐1 and upregulation of Keap1 genes and protein distribution along with significantly reduced levels of malondialdehyde and increased activity of superoxide dismutase, catalase and glutathione peroxidase in RN‐treated diabetic rats as compared to diabetic rats. Furthermore, treatment of diabetic rats with RN showed downregulated expression of tumour necrosis factor‐α, matrix metalloproteinase‐2 and upregulated expression of interleukin‐10 (IL‐10) and TIMP‐1 in the retina. RN treatment decreased nuclear factor kappa‐light‐chain‐enhancer of activated B cells distribution and increased IL‐10 protein distribution in the retinae of diabetic rats. In addition, RN treatment ameliorated morphological changes observed in retinae of diabetic rats. Altogether, these results provided clear evidence that treatment of diabetic rats with RN attenuated diabetic retinal changes through its hypoglycaemic, antioxidant and anti‐inflammatory effects.